Chlorophyll synthesis, growth and yield performance of summer mungbean CV. BARI MOOG-6 in response to BAP and NAA (Bangladesh Journal of Botany, 2021)
Effects of plant growth regulators (PGRs) on physiology, growth and yield attributes of summer mungbean (Vigna radiata L.) CV. BARI moog-6 were investigated. Two PGRs, namely NAA and BAP with three concentrations of each viz., 50, 100, 150 ppm and fresh water as control were applied as foliar spraying at vegetative and pre-flowering stage. Application of BAP and NAA had positive impact on the morphophysiological characteristics of summer mungbean. Spraying of PGRs at 150 ppm showed the highest performance regarding plant height, number of leaves per plant, leaf length, leaf breadth, root nodule number, chlorophyll and carotenoid contents, pod length, and seed yield of mungbean. Spraying BAP at 150 ppm concentration produced the highest seed yield (1.56 t/ha) followed by 150 ppm NAA (1.54 t/ha).Bangladesh J. Bot. 50(2): 209-217, 2021 (June)